N-(4-chlorophenyl)-N-(4,5-dihydro-1H-imidazol-2-yl) amine formamide solvate - Yildirim, Sema Oeztuerk; Akkurt, Mehmet; Servi, Sueleyman; Sekerci, Memet; Heinemann, Frank W. (Int Union Crystallography, 2007)
In the title compound, C9H10ClN3 center dot HC(O)NH2, the benzene and imidazole rings make a dihedral angle of 43.3 (1)degrees. In the crystal structure, molecules are linked through weak intermolecular N-H center dot center dot center dot O, N-H center dot center dot center dot N and C-H center dot center dot center dot N hydrogen bonds, forming a three-dimensional framework.
Keywords: Molecular-Structure; Crystal